Power Enhancement of Monocrystalline Solar Panel with Passive Cooling - Trifiananto, Muhammad; Hardiatama, Intan; Zainul Muttaqin, Aris; Edoward Ramadhan, Mochamad; Jatisukamto, Gaguk; Dimyati Nashrullah, Muhammad; Al Wafi, Adib (Universitas Muhammadiyah Sidoarjo, 2024)
The need for energy every year both in the domestic and global increases. Indonesia's energy needs are predicted to increase by 5% each year. Indonesia has renewable energy potential from solar, hydropower, wind, and geothermal sources. The potential of new renewable energy amounted to 442 GW. Of the 442 GW, the greatest potential is owned by 207 GW of solar energy. The high potential of solar energy in Indonesia is because Indonesia is located in the tropics which experiences sunshine time of approximately 6-8 hours per day and the sun continues to shine throughout the year. However, the length of irradiation also has an impact on increasing the temperature of solar panels. The higher the temperature of the solar panel, the output power will decrease and the life of the solar panel is reduced. The use of passive cooling from reference has a lower efficiency increase than active cooling. However, its installation requires lower costs, minimal maintenance, and no additional power requirements. This research will use 20WP monocrystalline solar panels with three cooling variations, namely: 1) with the addition of a thin aluminum plate and Vortex generator 2) By giving a tub of water under the panel 3) the Addition of aluminum fin. The three variations are compared with solar panels without cooling. The results on the first day showed a decrease in temperature of 2.30C with aluminum fin and an increase in power of 6.97% when using a water container. On the second day, a temperature decrease of 2.90C and a power increase of 5.81% when using aluminum fin coolers were recorded.